Green and Sustainable Development for TVET in Asia - Mustapha, Ramlee B (INVOTEC, 2015)
Green paradigm is emerging in Asia.  In order to achieve  sustainability, embracing green paradigm is critical.  The growing significance of sustainability is having a major impact on business, industry, and society as a whole. Hence, preparing the future workforce for the coming green economy is a challenging task for many Asian countries especially in Technical and Vocational Education and Training (TVET) in the post-2015 agenda.  As a ground work, transforming TVET in Asia to meet the challenges of the green economy for the purpose of sustainability should begin now.   The aim of this paper is to map the sustainable development in terms of green mindset, lifestyle, economy, education, training, employability and sustainability in selected Asian countries. A country’s quantum leap or leap-frogging in sustainable economy is dependent of its transformation of human resources especially in TVET sector. Thus, TVET should be transformed to fit the requirements of the sustainable green paradigm.  The results posit the country’s policies, best practices, and challenges toward green economy in order to achieve sustainable development.   Finally, the implication of green paradigm on TVET system in selected countries in the Asia Pacific will be discussed.